Implementasi Media Balok Putar Huruf Untuk Meningkatkan Kemampuan Mengenal Huruf Anak Usia 5-6 Tahun - Qudsi Mutawakil Husaini; Wahyudin; Risnayanti (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2025)
The ability to recognize letters is an important foundation in the process of learning to read for early childhood. However, there are still children who experience difficulties in recognizing letters due to a lack of interesting learning media. This study aims to describe the application of rotating letter blocks as a learning medium and its impact on the ability to recognize letters among 5–6-year-old children at Al-Hidayah Early Childhood Education Center. The research method employs a qualitative approach with a case study design. The research subjects are 12 children from Group B. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that this medium can enhance children's interest and understanding in recognizing letters through active and enjoyable learning. Some challenges that arose, such as tool damage and insufficient parental support, were successfully addressed with strategic solutions.